Patrimônio imaterial e a proteção jurídica dos dados pessoais - Stuart, Mariana Battochio (2023)
In a doctrinal, theoretical and jurisprudential perspective, the challenges for the realization of fundamental human rights related to the protection of personal data are discussed, in particular the offenses related to intangible heritage arising from consumer relations in contemporary Brazilian society. We intend to recognize the existence of a collective intangible heritage, examining the possibilities and challenges of obtaining and quantifying damages of this nature, in view of the basic principles that will guide the protection of the right to intimacy and privacy. The implementation of Compliance and ESG is proposed, understood as practices adopted by suppliers of products and services aiming at integrity and suitability in the processing of personal data of consumers as instruments for achieving economic and technological development in a lasting and sustainable way. As for the methodology used and the research methods employed, the deductive, inductive, documentary and historical methods were chosen, based on interdisciplinary research for the development and conclusion of the critical analysis on the proposed theme and the construction of the thesis that is intended to be defended. Finally, current primary and secondary sources will be surveyed regarding the issue of intangible heritage protection from the perspective of personal data protection